PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN BANARAN DAN DUSUN TERUKAN DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , M AULIA ARASY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final task is explains about measurement and mapping for mengasilkan a map that gives specific information or so-called spatial data from the earth's surface. Measurement methods implemented in this final project is a method of measuring frame horizontal control, vertical control framework method, measurements of planimetric detail, high point, as well as digital imaging. The result is a situation map the Earth's surface in the form of spatial data, Banaran Village and Terukan Village, Banyuripan Village, Bayat Sub-District, Klaten District, Central Java Province with a scale of 1: 500 in sisitem projection UTM (Universal Transverse Mercator).